Elasticity Optimism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
In most macroeconomic models, the substitutability between domestic and foreign goods is calibrated using aggregated data. This imposes homogeneous elasticities across goods, and the calibration is only valid under this assumption. If elasticities are heterogeneous, the aggregate substitutability is a weighted average of good-specific elasticities, which in general cannot be inferred from aggregated data. We identify structurally the substitutability in US goods using multilateral trade data. We impose homogeneity, and find an aggregate elasticity similar in value to conventional macroeconomic estimates. It is more than twice larger with sectoral heterogeneity. We discuss the implications in various areas of international economics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet